2016
DOI: 10.1073/pnas.1520665113
|View full text |Cite
|
Sign up to set email alerts
|

A topologically driven glass in ring polymers

Abstract: The static and dynamic properties of ring polymers in concentrated solutions remains one of the last deep unsolved questions in polymer physics. At the same time, the nature of the glass transition in polymeric systems is also not well understood. In this work, we study a novel glass transition in systems made of circular polymers by exploiting the topological constraints that are conjectured to populate concentrated solutions of rings. We show that such rings strongly interpenetrate through one another, gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
186
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(195 citation statements)
references
References 37 publications
8
186
1
Order By: Relevance
“…with this finding, several very recent works from different groups 12,[16][17][18] reported that rings in dense solutions display largely inter-penetrating configurations: segments of rings double-fold and thread through the contour of their neighbours, eventually leading to strongly overlapping configurations, perhaps best mimicked by the behaviour of ultra-soft colloids 19 rather than by that of polymers in poor solvents.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…with this finding, several very recent works from different groups 12,[16][17][18] reported that rings in dense solutions display largely inter-penetrating configurations: segments of rings double-fold and thread through the contour of their neighbours, eventually leading to strongly overlapping configurations, perhaps best mimicked by the behaviour of ultra-soft colloids 19 rather than by that of polymers in poor solvents.…”
Section: Introductionmentioning
confidence: 81%
“…The self-avoiding limit of the same system (randomly branched polymers) was instead shown 30 to display ν = 1/2 in 3D. Numerical 8,12,13 and experimental 31 evidence seem to suggest that the self-avoiding regime (ν = 1/2) in fact holds only for short rings, whereas the ideal behaviour (ν = 1/3) takes over in the limit of large polymerisation index through a broad crossover where 22 ν = 2/5. These arguments seem to lead to a picture of "crumpled lattice animals" where globally collapsed polymers display local tree-like structures.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations